Pemberdayaan Keluarga sebagai Upaya Pencegahan Kekambuhan Penderita Skizofrenia: Pengabdian - Wahyu Kirana; Yunita Dwi Anggreini; Dewin Safitri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Schizophrenia is a mental health problem with a high relapse rate, influenced in part by the family's ability to care for the patient. Families, as primary caregivers, play a crucial role in preventing relapse in schizophrenia patients. This community service activity aims to empower families in efforts to prevent relapse in schizophrenia patients. The method used was educational counseling and mentoring through interactive discussions with 20 families accompanying schizophrenia patients undergoing outpatient treatment at the West Kalimantan Provincial Mental Hospital. The activity was carried out on November 17, 2025, using leaflets containing information about schizophrenia, signs and factors of relapse, and the role of families in patient care. Evaluation was carried out through observation and discussion. The results of the activity showed an increase in family understanding regarding relapse prevention, medication adherence, and increased family confidence in carrying out their role as caregivers.